2023
DOI: 10.3390/polym15153170
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Assessment between Entrapment and Covalent Bond Immobilization of Mutant β-Xylosidase onto Chitosan Support

Gabriela Romero,
Lellys M. Contreras,
Carolina Aguirre Céspedes
et al.

Abstract: The Y509E mutant of β-xylosidase from Geobacillus stearothermophilus (XynB2Y509E) (which also bears xylanase activity) has been immobilized in chitosan spheres through either entrapment or covalent bond formation methods. The maximum immobilization yield by entrapment was achieved by chitosan beads developed using a 2% chitosan solution after 1 h of maturation time in CFG buffer with ethanol. On the other hand, the highest value in covalent bond immobilization was observed when employing chitosan beads that we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The reaction was stopped by the addition of 1 M Na 2 CO 3 . An extinction coefficient of ∆ε = 18 mM −1 cm −1 was used for pNP [20,21]. Glycerol inhibition was tested to concentrations of up to 50% (v:v).…”
Section: Activity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was stopped by the addition of 1 M Na 2 CO 3 . An extinction coefficient of ∆ε = 18 mM −1 cm −1 was used for pNP [20,21]. Glycerol inhibition was tested to concentrations of up to 50% (v:v).…”
Section: Activity Measurementsmentioning
confidence: 99%
“…Protein Engineering has been explored on the GH52 scaffold, allowing the introduction/improvement of xylanase [18] or glycosynthase activities [19]. A mutant form of XynB2 from Geobacillus stearothermophilus CECT43 also proved useful as an immobilized biocatalyst, such as cross-linked enzyme aggregates or covalently immobilized enzymes, resulting in pH stability and thermostability improvement of the biocatalyst [20,21]. These results suggest that β-xylosidase might be a good candidate for the generation of cross-linked enzyme crystals [22], for which protein crystallization is a mandatory pre-requisite.…”
Section: Introductionmentioning
confidence: 99%
“…Figure4apresents the enzymatic activity results obtained using T-GAC, and Figure4billustrates the results of the enzymatic activity of the T-ACBs with different GA concentrations and chitosan beads without activation.The immobilizations in GAC and chitosan beads mainly occurred via physical adsorption, so enzyme desorption is more accessible in case of operational changes. The ACBs' support was subjected to a chemical activation process with glutaraldehyde, a cross-linking agent, which introduces aldehyde functional groups into the chitosan spheres that form covalent bonds with the amine (NH 2 ) and thiol (SH) functional groups of tyrosinase[34]. Some authors have observed that during the immobilization of enzymes in GAC, the percentage of immobilized enzymes usually stabilizes under less than 120 min of contact between the enzyme and the support[28][29][30].…”
mentioning
confidence: 99%